Osteopontin mediates necroptosis in lung injury after transplantation of ischaemic renal allografts in rats. (October 2019) - Zhao, Hailin; Chen, Qian; Huang, Han; Suen, Ka C.; Alam, Azeem; Cui, Jiang; Ciechanowicz, Sarah; Ning, Jiaolin; Lu, Kaizhi; Takata, Masao; Gu, Jianteng; Ma, Daqing
Abstract: Background: Respiratory complications after surgery are associated with morbidity and mortality. Acute lung injury can result from the systemic inflammatory response after acute kidney injury. The mechanisms behind this remote injury are not fully understood. In this study, a renal transplantation model was used to investigate remote lung injury and the underlying molecular mechanisms, especially the role of osteopontin (OPN). Methods: In vitro, human lung epithelial cell line (A549) and monocyte/macrophage cell line (U937) were challenged with tumour necrosis factor-alpha (TNF-α) in combination with OPN. In vivo, the Fischer rat renal grafts were extracted and stored in 4°C University of Wisconsin preserving solution for up to 16 h, and transplanted into Lewis rat recipients. Lungs were harvested on Day 1 after grafting for further analysis. Results: Renal engraftment was associated with pathological changes and an increase in TNF-α and interleukin-1 beta in the lung of the recipient. OPN, endoplasmic reticulum (ER) stress, and necroptosis were increased in both the recipient lung and A549 cells challenged with TNF-α. Exogenous OPN exacerbated lung injury and necroptosis. Suppression of OPN through siRNA reduced remote lung injury by mitigation of ER stress, necroptosis, and the inflammatory response. Conclusions: Renal allograft transplant triggers recipient remote lung injury, which is, in part, mediated by OPN signalling. This study may provide a molecular basis for strategies to be developed to treat such perioperative complications.